Five models of scripture - Reasoner, Mark (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2021)
"A succinct guide to different models for engaging with Scripture, illustrated by examples from the history of interpretation"
Includes bibliographical references and index
Keywords: Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc